THE EFFECT OF WORD OF MOUTH AND BRAND IMAGE ON TRUST AND PURCHASE INTENTION - Endang Tjahjaningsih; Herina Dwi Nastiti; Sri Isnowati; Dewi Handayani UN (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
High consumer purchase intention can be obtained by trust built from Word Of Mouth (WOM) and brand image. This study aimed to reveal the effect of WOM and brand image on trust and purchase intention and the role of trust in mediating the effect of WOM and brand image on the purchase intention of Tokopedia consumers in Semarang City. The samples were obtained using a purposive sampling technique of 120 people. The data analysis technique used instrument, model, regression, and Sobel tests using the software of SPSS 24.0. Based on the primary data customers who were tested and analyzed, it has been proven that  (1) WOM and brand image have an effect on purchase intention, (2) WOM, brand image, and trust directly affect repurchase intention, (3) trust is mediating the relationship between WOM and brand image on purchase intention.